2005
DOI: 10.1207/s15327914nc5102_11
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the Growth of Premalignant and Malignant Human Oral Cell Lines by Extracts and Components of Black Raspberries

Abstract: Black raspberries are a rich natural source of chemopreventive phytochemicals. Recent studies have shown that freeze-dried black raspberries inhibit the development of oral, esophageal, and colon cancer in rodents, and extracts of black raspberries inhibit benzo(a)pyrene-induced cell transformation of hamster embryo fibroblasts. However, the molecular mechanisms and the active components responsible for black raspberry chemoprevention are unclear. In this study, we found that 2 major chemopreventive components… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
75
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(80 citation statements)
references
References 38 publications
4
75
0
1
Order By: Relevance
“…Only the alcohol fraction showed a dose-dependent decrease in ability of benzo[a]pyrene (B [a]P)-to induce transformation of Syrian hamster embryo (SHE) cells [42]. Similarly, Han, et al [43] found that the dichloromethane and alcohol fractions, and two known components; namely, ß-sitosterol and ferulic acid, selectively inhibited the growth of premalignant and malignant human oral cavity cell lines but not normal oral cells. They further found reduced levels of cyclin A and cell division cycle gene 2 (cdc2) in the premalignant cells, and reduced levels of cyclin B1, D1 and cdc2 in the malignant cells.…”
Section: In Vitro Studies With Berry Extractsmentioning
confidence: 98%
“…Only the alcohol fraction showed a dose-dependent decrease in ability of benzo[a]pyrene (B [a]P)-to induce transformation of Syrian hamster embryo (SHE) cells [42]. Similarly, Han, et al [43] found that the dichloromethane and alcohol fractions, and two known components; namely, ß-sitosterol and ferulic acid, selectively inhibited the growth of premalignant and malignant human oral cavity cell lines but not normal oral cells. They further found reduced levels of cyclin A and cell division cycle gene 2 (cdc2) in the premalignant cells, and reduced levels of cyclin B1, D1 and cdc2 in the malignant cells.…”
Section: In Vitro Studies With Berry Extractsmentioning
confidence: 98%
“…In a number of comparative studies with 'normal' cell lines some researchers have suggested that berry components may be selectively cytotoxic against cancer cells. Black raspberry extracts exerted a distinct differential effect on pre-malignant and malignant oral epithelial cells as compared to normal human oral epithelial cells at doses of 100-200 μg/ml (20). Cocoa extracts had a differential effect on prostate cancer cell lines DU145 and 22Rv1 compared to a normal prostate epithelial cell line (21).…”
Section: Introductionmentioning
confidence: 95%
“…Liesveld et al (48) found that quercetin showed no differential cytotoxic effects against normal CD34 + haematopoietic progenitor cells or acute myeloid leukemic cells (20). Sub-fractions of black raspberry extracts (20), probably enriched in anthocyanins, were selectively cytotoxic against pre-malignant and malignant oral cell lines but not against normal oral cell lines. However, another more hydrophobic sub-fraction, probably enriched in ellagitannins, was equally cytotoxic to normal, premalignant and malignant cells.…”
Section: ------------------------------------------------------------mentioning
confidence: 99%
See 1 more Smart Citation
“…, MEYERS et al, 2003, KATSUBE et al, 2003, OLSSON et al, 2004, HAN et al, 2005, SCHIMDT et al, 2005. Caracterização das diferentes cultivares de morango") no extrato total de morango os principais compostos fenólicos são as antocianinas e os derivados de ácido elágico.…”
Section: Tabela 18 Identificação Dos Derivados De áCido Elágico E Elunclassified